1992
DOI: 10.1063/1.858401
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic dynamics of particle dispersion in fluids

Abstract: An analysis of the Lagrangian motion for small particles denser than surrounding fluid in a two-dimensional steady cellular flow is presented. The Stokes drag, fluid acceleration, and added mass effect are included in the particle equation of motion. Although the fluid motion is regular, the particle motion can be either chaotic or regular depending on the Stokes number and density ratio. The implications of chaotic motion to particle mixing and dispersion are discussed. Chaotic orbits lead to the dispersion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 29 publications
2
41
1
Order By: Relevance
“…One of the observed features in these primarily computational studies is that for particles with a relatively fast inertial response, the particle trajectories asymptotically merge into a set of preferred paths. This settling and subsequent convergence is in contrast to the observed response for particles without inertia [Stommel (1949)] or the results of Crisanti et al (1990) or Wang et al (1992), who found chaotic motion for spherical and more general particles with large response times.…”
Section: Introductioncontrasting
confidence: 67%
“…One of the observed features in these primarily computational studies is that for particles with a relatively fast inertial response, the particle trajectories asymptotically merge into a set of preferred paths. This settling and subsequent convergence is in contrast to the observed response for particles without inertia [Stommel (1949)] or the results of Crisanti et al (1990) or Wang et al (1992), who found chaotic motion for spherical and more general particles with large response times.…”
Section: Introductioncontrasting
confidence: 67%
“…Various extensions of this basic model have been considered in the literature, in particular by Maxey and collaborators [14][15][16][17]29,37]. The equation of motion for a particle subject to the force (1.3) and molecular diffusion is…”
mentioning
confidence: 99%
“…16), the sign of the Stokes drift changes and the particles net displacement is directed toward the wave motion from left to right. At a distance lower than 5 mm from the bottom, the interaction between particle path and vorticity layer becomes intense and the mixing process is largely enhanced because of the chaotic nature of the Lagrangian advection and because of an anomalous dispersion (Wang et al 1992).…”
Section: Influence Of Roughness and Permeability On Trajectory Orbitsmentioning
confidence: 99%